Difference in antecedents of entrepreneurial intention between men and women: A study of Albanian university students - Makarova, Maria Alekseevna; Depperu, Donatella; Cambrea, Domenico Rocco; Sirianni, Camillo (Piccola Impresa / Small Business, 2024)
Purpose. This study examines the entrepreneurial intentions of male and female university students in Albania, which is a little-studied but interesting context due to a culture affected by both patriarchal values and a communist past. The main goal is to analyze the influence on entrepreneurial intention of individuals’ perceptions of possessing the characteristics required to be a successful entrepreneur as well as their perceptions of the need to sacrifice personal life to have a business, of the external macro-environment as a source (or not) of social guarantees and benefits, and of their fear of failure. Design/methodology/approach. The study used data from a survey of 447 students at seven Albanian universities. The authors employed a probit maximum likelihood model with robust standard errors to investigate the research hypotheses. Findings. The results reveal differences between the entrepreneurial intentions of female and male students and show that some under-researched perceptual variables explain the entrepreneurial intention and the influence of gender on it. Practical and Social Implications.The results give insights into the possible focus of policies aiming to enhance entrepreneurship among young women in Albania. Government policies should take into account the necessity to help women consider entrepreneurship as a possible career and encourage them to see themselves as capable of starting new ventures. Originality of the study. Considering the interplay of patriarchal values and Albania’s communist past, the results are inspiring for entrepreneurship research. Furthermore, the study focuses on under-researched variables and the moderating effect of gender on these variables.